The Communicative Function of Code-Switching and Code-Mixing in a Bilingual Digital Narrative - Alfin Rosyidha; Naila Rohmah; Girindra Putri Ardana Reswari; Fitri Alfarisy (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores the functions of code-switching in the digital discourse of Maudy Ayunda, an Indonesian public figure, particularly in her YouTube video “Thoughts on the Power of Language.” Utilizing a qualitative research approach, data were collected from her video that included both Indonesian and English. The analysis follows a systematic coding process based on Gumperz’s (1982) and Marasigan’s (1983) frameworks. Findings reveal that Maudy strategically employs code-switching to enhance engagement with diverse audiences, emphasize key points, and navigate between personal experiences and global perspectives. The study highlights the role of bilingual discourse as a powerful tool for identity construction and audience engagement in contemporary Indonesia, reflecting broader sociolinguistic trends where English proficiency is associated with educational and professional opportunities. Ultimately, this research contributes to a deeper understanding of how bilingual individuals leverage multiple languages in digital interactions to fulfill various communicative functions.